Lived experiences of stroke survivors in India: A phenomenological study - Manjula G Bhagavathy; Saravana Anniyappa; Radhakrishnan Thankappan; Bindhu Bharathi (Belitung Raya Foundation, Indonesia, 2022)
Background: Stroke is a major cause of long-term disability and has a potentially enormous emotional and socio-economic impact on patients, their families, and health services. Perceptions of patients with stroke have already been studied worldwide, which are unique in terms of their cultural background. However, in India, there is a lack of studies about the experience of the disease by stroke survivors and their perspectives of understanding the situation. Objective: This study aimed to explore lived experience of stroke survivors in India. Methods: A phenomenological study design was used. In-depth interviews were conducted with a purposive sample of ten stroke survivors who had experienced post-stroke deficits three months to one year after stroke. Data were analyzed using Diekelmann’s hermeneutical approach to identify underlying themes. Results: Two main themes emerged: (1) emergence of stroke (actual occurrence, mental perception, and recognition of illness) and (2) therapeutic concerns (enhanced and weakened recovery). Conclusion: Recognizing how patients experience the illness is crucial in planning care for stroke survivors. Strengthening factors enhancing recovery and limiting the hindering factors through effective therapeutic management is a necessity. The findings might also contribute to refining existing interventions and designing holistic multi-component rehabilitation programs that facilitate easy recovery. The study also highlights the need for providing information to general public on recognizing warning signs of stroke.